Total Testosterone and Sex Hormone-binding Globulin are Significantly Associated with Metabolic Syndrome in Middle-aged and Elderly Men - Chin, K.-Y.; Ima-Nirwana, S.; Mohamed, I. N.; Aminuddin, A.; Ngah, W. Z. W. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Testosterone and sex hormone-binding globulin (SHBG) have been shown to be associated with metabolic syndrome (MS) in men. This study aimed at validating these relationships in a group of middle-aged and elderly men and assessing their strength of association to MS. A cross-sectional study of 332 Malaysian men aged 40 years and above was conducted. The blood of subject was collected under fasting condition for determination of testosterone, SHBG, glucose and lipid levels. Their medical history, smoking and alcohol consumption status, waist circumference (WC), body mass index (BMI) and blood pressure (BP) were recorded. All testosterone and SHBG levels were significantly reduced in MS subjects compared to non-MS subjects (p<0.05). Testosterone and SHBG were correlated significantly with most of the MS indicators without adjustments. In multiple regression analysis, the triglyceride level was the only MS indicator that was significantly, inversely and independently associated with all testosterone measurements and SHBG (p<0.05). Waist circumference was significantly and negatively associated with SHBG level (p<0.05) though not independent of BMI. Total testosterone and SHBG were significantly and inversely associated with the presence of MS. Testosterone and SHBG are potential intervention targets for the prevention of MS in men.
Keywords: testosterone; sex hormone-binding globulin; metabolic syndrome; men